A rock physics model for analysis of anisotropic parameters in a shale reservoir in Southwest China. (23rd December 2015) - Qian, Keran; Zhang, Feng; Chen, Shuangquan; Li, Xiangyang; Zhang, Hui
Abstract: A rock physics model is a very effective tool to describe the anisotropy and mechanical properties of rock from a seismology perspective. Compared to a conventional reservoir, modelling a shale reservoir requires us to face two main challenges in modelling: the existence of organic matter and strong anisotropy. We construct an anisotropic rock physics workflow for a typical shale reservoir in Southwest China, in which the organic matter is treated separately from other minerals by using a combination of anisotropic self-consistent approximation and the differential effective medium method. The standard deviation of the distribution function is used to model the degree of lamination of clay and kerogen. A double scan workflow is introduced to invert the probability of pore aspect ratio and lamination simultaneously, which can give us a better understanding of the shale formation. The anisotropic properties of target formation have been analysed based on the proposed model. Inverted Thomsen parameters, especially the sign of delta, are analysed in terms of the physical properties of rock physics modelling.